Comprehensive candidate gene analysis for symptomatic or asymptomatic outcomes of Leishmania infantum infection in Brazil. (4th January 2017) - Weirather, Jason L.; Duggal, Priya; Nascimento, Eliana L.; Monteiro, Gloria R.; Martins, Daniella R.; Lacerda, Henio G.; Fakiola, Michaela; Blackwell, Jenefer M.; Jeronimo, Selma M. B.; Wilson, Mary E.
Summary: Genetic risk factors contribute to asymptomatic versus symptomatic visceral leishmaniasis (VL) outcomes following infection with Leishmania infantum . We therefore carried out a family‐based ( n = 918 post–quality control fully genotyped and phenotyped individuals) candidate gene study for symptomatic VL or asymptomatic delayed‐type hypersensitivity (DTH) skin test phenotypes in highly endemic neighborhoods of northeast Brazil. A total of 248 SNPs were genotyped in 42 genes selected as candidates on the basis of prior genetic, immunological, and transcriptional profiling studies. The most significant association with the VL phenotype was with SNP rs6785358 ( P = 5.7e‐04; pcorrected = 0.026) 3.8 kb upstream of TGFBR2, the gene encoding the type 2 receptor for transforming growth factor beta (TGFβ). A second inhibitory member of the TGBβ superfamily signaling pathway, SMAD7, was associated with the DTH phenotype (SNP rs7238442: P = 0.001; pcorrected = 0.051). The most significant association for the DTH phenotype was with SNP rs10800309 ( P = –8.4e‐06; pcorrected = 3.9e‐04) situated 3.1 kb upstream of FCGR2A, the gene encoding the low‐affinity IIa receptor for the Fc fragment of IgG. Overall, our results imply a role for IgG‐mediated inflammation in determining DTH associated with asymptomatic infection and contribute to growing evidence that the TGFβ pathway is important in the immunopathogenesis of VL.